MANAJEMEN KEUANGAN KELUARGA NASABAH PNM MEEKAR SYARIAH DALAM PERSPEKTIF EKONOMI ISLAM - Inayah Swasti Ratih; Sjafruddin Sjafruddin (Negotium: Jurnal Ilmu Administrasi Bisnis, 2023)
The purpose of this study is to determine the Islamic household financial management of PNM Meekar Syariah customers and provide an appropriate Islamic financial management model to manage family finances in an Islamic manner. The research method uses descriptive research with a qualitative approach. Research using descriptive methods is research that is directed to provide symptoms, facts accurately and systematically about the nature of certain regional populations. The results showed that the customer's understanding of household financial management was very simple. Customers have budgeting and apply financial management simply. Obstacles in its application due to uncertain income and low financial literacy owned. However, the research shows that the financial management of the three households studied is largely in accordance with the concept of Sakinah finance.